2011
DOI: 10.3727/096504011x13079697132961
|View full text |Cite
|
Sign up to set email alerts
|

Single-Agent Inhibition of Chk1 Is Antiproliferative in Human Cancer Cell Lines In Vitro and Inhibits Tumor Xenograft Growth In Vivo

Abstract: Chk1 is a serine/threonine kinase that plays several important roles in the cellular response to genotoxic stress. Since many current standard-of-care therapies for human cancer directly damage DNA or inhibit DNA synthesis, there is interest in using small molecule inhibitors of Chk1 to potentiate their clinical activity. Additionally, Chk1 is known to be critically involved in cell cycle progression of unperturbed cells. Therefore, it is plausible that treatment with a Chkl inhibitor alone could also be an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 0 publications
8
33
0
Order By: Relevance
“…Genomic damage resulting from deregulated DNA replication, determined by gH2AX staining in S-phase cells, is not only a hallmark of the response to WEE1 monotherapy (described here) but also both the combination of the WEE1 and CHK1 inhibitors and CHK1 inhibitor monotherapy (42). Our own work supports the in vivo combination benefit from combined WEE1 and CHK1 inhibition (data not shown; ref.…”
Section: Discussionsupporting
confidence: 74%
“…Genomic damage resulting from deregulated DNA replication, determined by gH2AX staining in S-phase cells, is not only a hallmark of the response to WEE1 monotherapy (described here) but also both the combination of the WEE1 and CHK1 inhibitors and CHK1 inhibitor monotherapy (42). Our own work supports the in vivo combination benefit from combined WEE1 and CHK1 inhibition (data not shown; ref.…”
Section: Discussionsupporting
confidence: 74%
“…As shown in previous chapters of this thesis and also in previous reports of CHK1i (King et al, 2015, Brooks et al, 2013, Davies et al, 2011b, Walton et al, 2012, only a subset of tumour cell lines is sensitive to CHK1i single-agent treatment and there is significant proportion of tumour cell lines which are not sensitive to singleagent treatment. Here, low-dose hydroxyurea (0.2 mM) was added concurrently with CHK1i to induce replication stress in the melanoma cells and sensitise them to CHK1i inhibition.…”
Section: Discussionsupporting
confidence: 72%
“…Thus, there is a significant portion of melanoma patients who are still in need of effective treatments. CHK1 inhibitor (CHK1i) single-agent treatment was found to be cytotoxic to various melanoma cell lines and other cancer cell lines as reported in previous chapters in this thesis and other reports (King et al, 2015, Brooks et al, 2013, Davies et al, 2011b, Walton et al, 2012. I have found that CHK1i hypersensitivity is associated with defective S phase checkpoint arrest in melanoma cells, and the majority of the CHK1i-hypersensitive cell lines have an uncoupling of checkpoint activation and CDC25A degradation that is largely responsible for the S phase arrest, as discussed in Chapter 3 of this thesis.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations